The outcomes of the extracardiac total cavopulmonary connection in 130 consecutive patients with single-ventricle physiology - E. M. Bairamov; Y. V. Poznyak; O. M. Dovgan; N. M. Rudenko; I. M. Yemets (Ukrainian Journal of Cardiovascular Surgery, 2017)
Fontan procedure has gone through several modifications and today is the primary palliation to treat a broad spectrum of com-plex congenital heart defects.The aim of this study is to present the results of treatment of children and adults with a single ventricle.Materials and methods. Since 2005 to 2015 years, in 130 consecutive patients with a single ventricle morphology aged 9,97±4,37 years the extracardiac total cavopulmonary connection was performed. The most common heart pathology was tricus-pid atresia (26,9%). In 118 (90,8%) patients, the operation was carried out with the moderately hypothermic cardiopulmonary bypass, without aortic cross-clamp. The average cardiopulmonary bypass time was 94,2±56,6 min. In the remaining twelve patients extracardiac TCPC was carried out without CPB.Results. There were three (2,3%) early deaths. The median duration of the mechanical ventilation was 9,7±16,1 h (1–71 h). The average length of stay was 17,5±18,5 days (8,0–81,0 days).Conclusions. Improved understanding of single-ventricle physiology, patient preparation, surgical techniques, and post-operative care has allowed us to reach a steady state in the early outcomes after TCPC.